Cardiovascular Comorbidity: Patient with Coronary Artery Disease and Peripheral Artery Atherosclerosis. How to Identify and Manage the Risks of Ischemic Events? - O. L. Barbarash; V. V. Kashtalap; I. A. Shibanova (Рациональная фармакотерапия в кардиологии)
Modern data on comorbidity in coronary artery disease (CAD) are presented in the article, as well as its frequency, dependence on the age, clinical and prognostic significance, and increasing relevance for practical health care. The positions of one of the components of cardiovascular comorbidity – multifocal atherosclerosis – are presented. The existing approaches to the detection and clinical assessment of multifocal atherosclerosis, as well as to the management of the high risk of ischemic events in such patients, are outlined. The main positions on the prevention of the risk of cardiovascular complications in patients with CAD and atherosclerosis of the peripheral arteries using a combination of the anticoagulant – rivaroxaban and the antiplatelet agent – acetylsalicylic acid, are highlighted on the basis of the results of clinical studies. Promising possibilities of using such a therapeutic approach to the management of comorbid patients in routine clinical practice are presented.